Calculation and field measurement of earth pressure in shield tunnels under the action of composite foundation - Zhang, Chi; Ma, Shi-ju; Guo, Yuan-cheng; Li, Ming-yu; Safaei, Babak (Techno-Press, 2023)
Taking a subway shield tunnel in a certain section of Zhengzhou Metro Line 5 as an example, the field tests of shield cutting cement-soil monopile composite foundation were carried out. The load and internal force of the tunnel lining under the action of composite foundation were tested on-site and the distribution characteristics and variation laws of earth pressure around the tunnel under the load holding state of the composite foundation were analyzed. Five different load combinations (i.e., overburden load theory + q0, Terzaghi's theory + q0, Bierbaumer's theory + q0, Xie's theory + q0, and the proposed method (the combination of compound weight method and Terzaghi's theory) + q0) were used to calculate the internal force of the tunnel structure and the obtained results were compared with the measured internal force results. The action mode of earth pressure on the tunnel lining structure was evaluated. Research results show that the earth pressure obtained by the calculation method proposed in this paper was more consistent with the measured value and the deviation between the two was within 5%. The distribution of the calculated internal force of the tunnel structure was more in line with the distribution law of field test data and the deviation between the calculated and measured values was small. This effectively verified the rationality and applicability of the proposed calculation method. Research results provided references for the design and evaluation of shield tunnels under the action of composite foundations.
Keywords: earth pressure; existing composite foundation; field monitoring; shield tunnel; theoretical calculation methods